Proved wireless sensor networks time synchronization algorithm based on RBS - LI Wen-feng 1; WANG Ru-chuan1; SUN Li-juan1 (Tongxin xuebao)
IRBS algorithm was proposed on RBS.According to receiver node time,IRBS estimate its real time.During its calculation of two nodes time difference,it realizea time synchronization by the estimating time.Simulation result shows IRBS algorithm can reduce time error and improve time synchronization precision.